Investor-state dispute settlement: A government's dilemma - Joachim Karl (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2013)
The landscape in which investor-state dispute settlement (ISDS) takes place is undergoing profound change. Although discontent with the current ISDS system is on the rise, most countries have so far not seen a need to modify ISDS provisions in international investment agreements. To move forward, countries should take a pro-active approach toward reforming the ISDS mechanism.
Keywords: 330